2023
DOI: 10.1002/eqe.4053
|View full text |Cite
|
Sign up to set email alerts
|

Automated parameterization of velocity pulses in near‐fault ground motions

Zhiwang Chang,
Haoran Wu,
Katsuichiro Goda

Abstract: Proper parameterization of near‐fault ground motions is of critical importance in earthquake engineering, and this process is traditionally performed by directly fitting an analytical pulse model to the original motion. Yet such a process is usually limited by the trial‐and‐error procedure, which is strongly dependent on the initial guesses and may converge to local rather than global minimums. In this study, we propose a progressive (step‐by‐step) iterative approach that can achieve a fully automated paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 122 publications
0
6
0
Order By: Relevance
“…There have been a couple of studies (e.g., Hu et al, 2024;Ertuncay and Costa, 2024) analyzing the strong pulse-like features observed in the 2023 Türkiye earthquake sequence, of which the algorithm by Shahi and Baker (2014) was frequently used to identify if there are significant pulses contained in the velocity time histories. In this study, the approach newly proposed by Chang et al (2024a) is employed. Compared with previous studies (e.g., Baker, 2007;Shahi and Baker, 2014;Zhai et al, 2018;Chen et al, 2019;Feng et al, 2021;Tang et al, 2022;Zhao et al, 2023) that solely focused on the identification of pulse-like characteristics, the velocity pulses of interest observed in the 2023 Türkiye earthquake sequence are here not only quantitatively identified but are also fully parameterized.…”
Section: Parameterization Of Velocity Pulsesmentioning
confidence: 99%
See 4 more Smart Citations
“…There have been a couple of studies (e.g., Hu et al, 2024;Ertuncay and Costa, 2024) analyzing the strong pulse-like features observed in the 2023 Türkiye earthquake sequence, of which the algorithm by Shahi and Baker (2014) was frequently used to identify if there are significant pulses contained in the velocity time histories. In this study, the approach newly proposed by Chang et al (2024a) is employed. Compared with previous studies (e.g., Baker, 2007;Shahi and Baker, 2014;Zhai et al, 2018;Chen et al, 2019;Feng et al, 2021;Tang et al, 2022;Zhao et al, 2023) that solely focused on the identification of pulse-like characteristics, the velocity pulses of interest observed in the 2023 Türkiye earthquake sequence are here not only quantitatively identified but are also fully parameterized.…”
Section: Parameterization Of Velocity Pulsesmentioning
confidence: 99%
“…Compared with previous studies (e.g., Baker, 2007;Shahi and Baker, 2014;Zhai et al, 2018;Chen et al, 2019;Feng et al, 2021;Tang et al, 2022;Zhao et al, 2023) that solely focused on the identification of pulse-like characteristics, the velocity pulses of interest observed in the 2023 Türkiye earthquake sequence are here not only quantitatively identified but are also fully parameterized. Specifically, four physical parameters for defining the waveform characteristics of the underlying pulses are determined using the approach in Chang et al (2024a). The parameterization of velocity pulses has various engineering applications, e.g., the stochastic simulations of near-fault ground motions (e.g., Yang and Zhou, 2015;Yadav and Gupta,2017;Dabaghi and Kiureghian, 2017) and the parametric investigations of the effects of velocity pulses on different structures (e.g., Kalkan and Kunnath, 2006;Rupakhety and Sigbjörnsson, 2011;Khoshnoudian and Ahmadi, 2013;Wu et al, 2014;Alonso-Rodríguez and Miranda, 2015).…”
Section: Parameterization Of Velocity Pulsesmentioning
confidence: 99%
See 3 more Smart Citations